The effects of spiritual leadership on organizational trust : a study amongst university's administrators - Mohamad Fadzil, Samiran (2024)
The purpose of this study is to examine the effect of spiritual leadership on organizational trust among administrative and support staff at Universiti Utara Malaysia. A stratified random sampling technique was used in data collection, with a sample size of 306 appropriate to a total of 1470 population. The retrieved data was analyzed using the statistical package of social science SPSS, and thus, factor analysis and multiple regression analysis were executed to examine the significant effect between the study variables. Also, this study used both descriptive and inferential statistics to analyze data. This study revealed that, from factor analysis results, spiritual leadership is represented by altruistic love and hope while organizational trust is encompassed with three dimensions namely leader reliance, leader behavior, and harmony. Altruistic love refers to the character of a leader who always takes care of his employees’ rights and benefits as well as courteous in communication. As for hope, this dimension is defined as employees' confidence that their leader has a clear vision for achieving the corporate aspiration. The multiple regression results found that altruistic love only significantly affected a leader’s reliance while hope significantly influenced all three dimensions of organizational trust which are leader’s reliance, leader’s behavior, and harmony. This study contributes to the literature on how spiritual leadership influences organizational trust particularly in Universiti Utara Malaysia and generally in public universities in Malaysia. Lastly, study implications, limitations, conclusion as well as suggestions for the university’s management were discussed